The Attributes of a Person Participating in Arts and Cultural Heritage Conservation in the Multicultural Context of the Southern Border Area, Narathiwat Province, Thailand - Tepsing, Punya; Laeheem, Kasetchai (International Journal of Membrane Science and Technology, 2023)
The objective of this research is to study the attributes of a person participating in arts and cultural heritage conservation in the multicultural context of the Southern border area, Narathiwat province, Thailand, by using the qualitative method. Data were collected from both documents and in the field from the three districts of Narathiwat province with distinctive Thai, Chinese, and Melayu art and culture. An in-depth interview was applied to the 41 main informants, including (1) 30 Thai, Chinese, and Melayu of the arts and cultural worker group in the three districts of Narathiwat province, (2) 6 academics of arts and cultural heritage, and (3) 5 community leaders. Data source triangulation was used to test the reliability. The result of the descriptive analysis was that the attributes of a person participating in arts and cultural heritage conservation is a person who (1) loves his locality, (2) is open-minded, (3) sees common interests first, (4) is educated or knowledgeable, and (5) has leadership skills.